2020
DOI: 10.1177/0363546520951529
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Ulnar Collateral Ligament Revision Reconstruction in Baseball Players

Abstract: Background: There is a lack of evidence regarding the success of ulnar collateral ligament (UCL) revision reconstruction. Understanding outcomes after UCL revision reconstruction is important in clinical decision making for overhead athletes. Purpose: To evaluate return to play and patient-reported outcomes after UCL revision reconstruction. Study Design: Case series; Level of evidence, 4. Methods: All patients who underwent UCL revision reconstruction, attributed to retear of the ligament or pain, between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…The same cannot be said after reruptures of the previously reconstructed graft. Andrews et al 1 reported that of a series of 40 pitchers from various levels in an institutional database, 80% were able to return to baseball, but only 47% returned to the same level of competition (reported as a Conway score of excellent). Of the 10 MLB pitchers included in that study, 80% reported excellent Conway scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same cannot be said after reruptures of the previously reconstructed graft. Andrews et al 1 reported that of a series of 40 pitchers from various levels in an institutional database, 80% were able to return to baseball, but only 47% returned to the same level of competition (reported as a Conway score of excellent). Of the 10 MLB pitchers included in that study, 80% reported excellent Conway scores.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort of pitchers returned to professional competition at a mean of 17.0 ± 6 months, consistent with other similar reported series. Andrews et al 1 reported pitchers of all levels returning to competition at a mean of 12.8 ± 3.7 months, while the MLB pitchers took 14.5 months (range, 10-21 months). Camp et al 5 reported that their cohort of professional pitchers returned to the same level of competition at 16.1 ± 3.9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While revision rates may vary among positions in baseball, it is well-established that decreased performance and career longevity are significantly diminished after surgery, making the focus of clinical outcomes after primary UCLR of paramount impact. 3 , 26 …”
mentioning
confidence: 99%
“…While revision rates may vary among positions in baseball, it is well-established that decreased performance and career longevity are significantly diminished after surgery, making the focus of clinical outcomes after primary UCLR of paramount impact. 3,26 A number of risk factors for excessive UCL stress and potential UCL injury or reinjury have been identified in the literature: glenohumeral range of motion measures, 16,40 measures of throwing volume, 1,34 kinetic chain deficits, 15,18 and parameters of pitching performance. 2,4,13,29,31,39 Decreases in rotator cuff strength have also been linked to risk for elbow injury.…”
mentioning
confidence: 99%